A REVIEW OF NAGUIB MAHFOUZ’S ‘THE BEGGAR’ BASED ON NORMAN FAIRCLOUGH'S CRITICAL DISCOURSE ANALYSIS - Hosseini, Abdollah; Sattari, Elaheh (PEOPLE: International Journal of Social Sciences, 2018)
In a sense, critical discourse is considered an approach that goes beyond mere description of linguistic data to concentrate on the instrumental processes involved in the formation of discourse. This type of criticism consists of two approaches: social and linguistic: the former deals with the situational context while the latter describes the textual context. The present paper, using the descriptive-analytical method, attempts to investigate the linguistic, ideological and social aspects of ‘The Beggar’ at the levels of description, interpretation and explanation in light of Norman Fairclough’s critical discourse Analysis, with the purpose of understanding the sociological elements of this novel along with its interpretations; and, appreciating the effect of sociological context on the novel and the processes which allow the emergence of such a novel. Mahfouz wrote ‘The Beggar’ at a point of his life when some were committed to the Revolution and its conditions, while others remained silent. The results of the study indicate that Mafhouz has created a remarkable harmony between the social concepts and linguistic features of the novel. Relying on lingual devices such as Arabic interrogative, nominal and rhetoric sentences, he has projected his intended meanings across the superstructure of the text including descriptions, humorous tone and interior monologues, etc. Hence, he has been able to portray concepts such as ideology and culture, restrictions and influential processes of the Egyptian society in his literary work. Throughout ‘The Beggar’, Mahfouz illustrates all the events and crises of the Egyptian society on different political and social levels from the subjective symbolism and social criticism perspectives. This research seeks to examine this novel at three levels of description, interpretation, and explanation.